2022
DOI: 10.3892/mmr.2022.12776
|View full text |Cite
|
Sign up to set email alerts
|

Hyperoside ameliorates TNF‑α‑induced inflammation, ECM degradation and ER stress‑mediated apoptosis via the SIRT1/NF‑κB and Nrf2/ARE signaling pathwaysin vitro

Abstract: intervertebral disc degeneration (idd) is the main pathogenesis of numerous cases of chronic neck and back pain, and has become the leading cause of spinal-related disability worldwide. Hyperoside is an active flavonoid glycoside that exhibits anti-inflammation, anti-oxidation and anti-apoptosis effects. The purpose of the present study was to investigate the effect of hyperoside on tumor necrosis factor (TnF)-α-induced idd progression in human nucleus pulposus cells (nPcs) and its potential mechanism. The act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 47 publications
(37 reference statements)
0
1
0
Order By: Relevance
“… 84 Se reversed the excessive apoptosis of NP cells induced by TBHP via reducing the excessive production of intracellular ROS and the increase of malondialdehyde (MDA) level, as well as upregulating the expression of superoxide dismutase 2 (SOD2). 85 In addition, with the development of research, an increasing number of molecules have been shown to protect IVD cells from mitochondrial dysfunction and apoptosis by activating Nrf2 signaling, including VO-OHpic, 86 Andrographolide, 87 hyperoside, 88 Amobarbital 9 and Procyanidin B2. 89 …”
Section: Therapeutic Strategies By Targeting Nrf2mentioning
confidence: 99%
“… 84 Se reversed the excessive apoptosis of NP cells induced by TBHP via reducing the excessive production of intracellular ROS and the increase of malondialdehyde (MDA) level, as well as upregulating the expression of superoxide dismutase 2 (SOD2). 85 In addition, with the development of research, an increasing number of molecules have been shown to protect IVD cells from mitochondrial dysfunction and apoptosis by activating Nrf2 signaling, including VO-OHpic, 86 Andrographolide, 87 hyperoside, 88 Amobarbital 9 and Procyanidin B2. 89 …”
Section: Therapeutic Strategies By Targeting Nrf2mentioning
confidence: 99%